2018
DOI: 10.12707/riv17078
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and associated risk factors in independent older people living in rural areas

Abstract: Fragilidade e fatores de risco associados em pessoas idosas independentes residentes em meio ruralFrailty and associated risk factors in independent older people living in rural areas Fragilidad y factores de riesgo asociados en personas ancianas independientes residentes en el medio rural AbstractBackground: The diagnosis of the frailty syndrome is essential in the planning of elderly health interventions. Objective: To assess the prevalence of frailty among older people living in rural communities and its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
1
1
2
Order By: Relevance
“…Among older adults in the frailty process, there was a higher prevalence of men (64.4 %; n = 161), diverging from other studies (18)(19)(20), that found a higher prevalence in women. In fact, the female gender is considered a risk factor for frailty (21).…”
Section: Discussioncontrasting
confidence: 88%
“…Among older adults in the frailty process, there was a higher prevalence of men (64.4 %; n = 161), diverging from other studies (18)(19)(20), that found a higher prevalence in women. In fact, the female gender is considered a risk factor for frailty (21).…”
Section: Discussioncontrasting
confidence: 88%
“…Os achados do nosso trabalho sugerem que os idosos fragilizados apresentavam mais comorbidades, em linha com as evidências de outros estudos (SANTOS, et al, 2023;PRETO, et al, 2018). Sabe-se que a probabilidade de surgimento de déficits biológicos e doenças aumenta durante o processo de envelhecimento e a literatura enfatiza a diminuição de qualidade de vida relacionada com a saúde e a alta prevalência de doenças crónicas em pessoas muito idosas (STRANDBERG, et al, 2011).…”
Section: Discussionunclassified
“…No contexto demográfico europeu observamos uma realidade marcada pelo envelhecimento populacional, sendo que em Portugal existem 151 pessoas com mais de 65 anos de idade por cada 100 jovens, o que prioriza o correto diagnóstico das situações de saúde do idoso, como por exemplo a condição de fragilidade da pessoa idosa (PRETO., 2018).…”
Section: Introductionunclassified
“…Eating patterns also seem to correlate with the frailty states. Especially in industrialized countries, body weight and body mass index (BMI) are increasing in people aged between 60 and 80 years [ 13 ]. Several studies have examined the association between eating patterns and frailty, showing that a diet rich in fruits, vegetables, and whole grains may be related to a reduced risk of frailty [ 14 ].…”
Section: Introductionmentioning
confidence: 99%